CHARA CONTRARIA BRAUN EX KÜTZ (1845) (CHARACEAE): A NEW RECORD FOR IRAQ - ALazawy , M. R (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The current study aimed to record and describes the alga Chara contraria moss for the first time in Iraq, where this algae was collected in Al-Ishaqi irrigation project and its small cement-lined branches north of Baghdad within the governorate of Salah Al-Din, Al-Sheikh Jameel village, for the year 2023-2024 during the winter. The exploratory method was used in order to obtain this algae, where the alga was placed in sterile plastic bottles, kept in formalin solution, extracted and placed on a white paper, measured the length of the alga, calculated the branches with the help of a digital camera, and measured some physicochemical changes on water samples. The results of the tests showed that the water of the project in which algae grows basal with a pH rate of 8.05 and total dissolved substances 189 mg/L and electrical conductivity of 351.5 microsimins/cm, while the total hardness recorded 140 included high concentrations of calcium 40 mg/L compared to magnesium concentration of 9.7 mg/L, while nutrients recorded high values ranging between (0.010-0.087) mg/L, (0.010-0.087), mg/L, (0.227-1.450) mg/L and (0.02-6.30) mg/L for both dissolved phosphates and sulfates, nitrates and silicates, respectively.